Preparation and application of natural biomass water retention gel for water collection and water retention of arid soil

By preparing natural biomass hydrocarbons with porous structures, the problem of insufficient water collection capacity in arid soils is solved, and the effect of improving soil water absorption and improving plant growth is achieved.

CN119775599AActive Publication Date: 2025-04-08SOUTHWEAT UNIV OF SCI & TECH

Patent Information

Application Number
CN202411988302.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The existing biomass-based porous hydrogel materials lack water collection capacity in arid soil, and have poor water absorption and water release properties, making it difficult to effectively improve the water absorption of the soil and improve the growth of plants under drought conditions.

Method used

Sodium alginate (SC) and carboxymethylcellulose (CMC) were used as matrix, and natural biomass hydrocarbons (SC-LiCl/PNIPAM gel beads) with porous structure were prepared by adding lithium chloride, N-isopropyl acrylamide monomer (NIPAM) and polymerization accelerator, and gel beads were obtained through microfluidic control and vacuum freeze-drying.

Benefits of technology

It improves the water absorption and water circulation stability of arid soils, enhances the ability to capture water from the atmosphere, improves the growth of plants under drought conditions, and reduces the impact of drought stress on plants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775599A_ABST
    Figure CN119775599A_ABST
Patent Text Reader

Abstract

The invention discloses preparation and application of natural biomass water retention gel for water collection and retention of arid soil, and the preparation method comprises the following steps: dissolving sodium alginate and carboxymethyl cellulose in deionized water, and then adding lithium chloride, an N-isopropylacrylamide monomer and N, N '-dimethyl diacrylamide to obtain a mixture; foaming the mixture with Ar gas, then adding N, N, N ', N'-tetramethylethylenediamine, a polymerization accelerator and ammonium peroxide as initiators, and polymerizing to obtain mixed gel; dropwise adding the mixed gel into a calcium chloride aqueous solution through a microfluidic method to obtain hydrogel beads, washing and drying to obtain the natural biomass water-retaining gel. The natural biomass water retention gel contains a three-dimensional porous structure, enhances adsorption-desorption kinetics, and effectively inhibits aggregation of hygroscopic salt-LiCl particles in a hydration process, so that good water absorption performance and cycling stability are realized, water vapor can be extracted from arid climate, and water can be effectively captured from atmosphere.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogels, and in particular relates to the preparation and application of a natural biomass water-retaining gel for collecting and retaining water in arid soil. Background Art

[0002] It is well known that water resources play an indispensable role in vegetation restoration, and traditional irrigation methods, such as sprinklers, sprays, and drip systems, face certain limitations when implemented in areas such as slopes. Therefore, the development of new water harvesting systems aims to meet the hydraulic needs of electronic vegetation restoration on railway slopes more efficiently and sustainably. Atmospheric water harvesting (AWH) is considered to be a promising method that aims to solve the global water shortage problem by extracting water from the air, and is particularly suitable for arid and water-scarce areas. Biomass-based porous hydrogel materials are considered to be ideal absorbent materials and have been used for AWH over a wide humidity range, especially at low relative humidity (≥30%). However, biomass-based porous hydrogel materials are generally limited by their low water collection capacity and incomplete water desorption. Therefore, it is necessary to develop an absorbent material that can be used in arid soils to improve soil water absorption and solve the problems of poor water absorption capacity and incomplete water release of traditional water harvesting materials. Summary of the invention

[0003] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.

[0004] In order to achieve these purposes and other advantages according to the present invention, a method for preparing a natural biomass water-retaining gel for water collection and retention in arid soil is provided, comprising the following steps:

[0005] Step 1, dissolving sodium alginate (SC) and carboxymethyl cellulose (CMC) in deionized water, stirring and mixing, then adding lithium chloride (LiCl), and then continuing to add N-isopropylacrylamide monomer (NIPAM) and N,N'-dimethylbisacrylamide under stirring conditions to obtain a mixture;

[0006] Step 2: bubbling the mixture with Ar gas, and then sequentially adding N,N,N',N'-tetramethylethylenediamine, a polymerization accelerator and ammonium peroxodisulfate as an initiator, completing polymerization at room temperature to obtain a mixed gel;

[0007] Step 3: The mixed gel is dropped into a calcium chloride aqueous solution at 60° C. by a microfluidic method and reacted for a period of time to obtain hydrogel beads, and then the hydrogel beads are washed with deionized water, and finally vacuum freeze-dried to obtain SC-LiCl / PNIPAM (SCLP) gel beads, i.e., natural biomass water-retaining gel, wherein PNIPAM represents the product after NIPAM polymerization.

[0008] Preferably, in step 1, the mass ratio of sodium alginate, carboxymethyl cellulose, deionized water, lithium chloride, N-isopropylacrylamide monomer and N,N'-dimethylbisacrylamide is 2:1:100:0.56:5-20:0.006.

[0009] Preferably, in step 2, the Ar gas bubbling time is 60 min, the amount of N,N,N',N'-tetramethylethylenediamine added is 12-60 μL, the polymerization accelerator is N,N'-methylenebisacrylamide crosslinker (MBA), the amount added is 6-24 mg, the amount of ammonium peroxydisulfate added is 20-80 mg, and the polymerization time is 24 h.

[0010] Preferably, in step 3, the concentration of the calcium chloride aqueous solution is 0.34 g / mL, the reaction is performed for 12 hours, the vacuum freeze-drying temperature is -60°C, and the freezing time is 48 hours.

[0011] Preferably, the lithium chloride is first modified by:

[0012] S1, dissolving lithium chloride in ethanol, heating and stirring until the lithium chloride is completely dissolved to prepare a lithium chloride solution, then adding dopamine thereto, keeping the temperature for a period of time to react, and obtaining a polydopamine-lithium chloride gel;

[0013] S2. Carbonizing the polydopamine-lithium chloride gel at high temperature, and then performing argon plasma etching after the carbonization is completed to obtain modified lithium chloride.

[0014] Preferably, in S1, the concentration of the prepared lithium chloride solution is 50-80wt%, the mass ratio of lithium chloride to dopamine is 1:0.2-0.5, the reaction temperature is 75-110°C, and the reaction is kept warm for 6-12h.

[0015] Preferably, in S2, the high-temperature carbonization temperature is 500-800°C, the carbonization time is 0.5-2h, the argon plasma etching time is 5-500s, the power is 60-120W, and the pressure is 20-80Pa.

[0016] The present invention also provides an application of a natural biomass water-retaining gel in water collection and water retention in arid soil. The natural biomass water-retaining gel is used in arid soil to improve the water absorption and temperature sensitivity of the arid soil.

[0017] The present invention includes at least the following beneficial effects: the matrix of the natural biomass water-retaining gel prepared by the present invention is composed of cheap, scalable, non-toxic biomaterials sodium alginate (SA) and carboxymethyl cellulose (CMC), which give the hydrogel a three-dimensional porous structure, thereby enhancing the adsorption-desorption kinetics. At the same time, the SA / CMC network effectively inhibits the aggregation of hygroscopic salt-LiCl particles during the hydration process, thereby achieving good water absorption performance and cyclic stability performance, which is conducive to extracting water vapor from arid climates, can effectively capture moisture from the atmosphere, change the distribution of dominant populations in soil communities, and enhance the activity of defense enzymes, thereby alleviating the widespread impact of drought stress on plant growth, and providing a feasible prospect for large-scale production of hygroscopic hydrogels and ecological restoration of barren slopes.

[0018] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The figure is a synthesis process diagram of the natural biomass water-retaining gel of the present invention;

[0020] Figure 2 The SEM images of the SCLP gel beads prepared in Example 1 of the present invention at different magnifications;

[0021] Figure 3 Energy dispersive x-ray spectroscopy (EDS) of SCLP gel beads prepared in Example 1 of the present invention;

[0022] Figure 4 FTIR spectra of SCLP gel beads prepared in Example 1 of the present invention, SCL gel beads prepared in Comparative Example 1, SC gel beads prepared in Comparative Example 3, and PNIPAM;

[0023] Figure 5 XRD patterns of SCLP gel beads prepared in Example 1 of the present invention, SCL gel beads prepared in Comparative Example 1, SC gel beads prepared in Comparative Example 3, and PNIPAM;

[0024] Figure 6 This is the total XPS spectrum of the SCLP gel beads prepared in Example 1 of the present invention;

[0025] Figure 7 This is a high-resolution XPS spectrum of the SCLP gel beads prepared in Example 1 of the present invention;

[0026] Figure 8 This is a diagram of the swelling performance of Examples 1-4 of the present invention at different temperatures;

[0027] Fig. 9The water contact angle diagram of the SCLP gel beads prepared in Example 1 of the present invention at different temperatures;

[0028] Fig.10 TG curves of Example 1 of the present invention, Comparative Examples 1 and 3, and PNIPAM;

[0029] Fig.11 The compressive stress-strain curves of Example 1 and Comparative Examples 1 and 3 of the present invention are shown;

[0030] Fig.12 This is a graph showing the water absorption performance of SCLP gel beads prepared in Example 1 of the present invention at different humidity levels;

[0031] Fig.13 A weight change diagram of the SCLP gel beads prepared in Example 1 of the present invention during a water vapor adsorption-release cycle and a digital photograph of the SCLP beads during a water vapor adsorption-desorption cycle;

[0032] Fig.14 This is a graph of atmospheric water collection and water release of SCLP gel beads prepared in Example 1 of the present invention during nighttime cycles;

[0033] Fig.15 This is a graph showing the water vapor adsorption performance of the SCLP gel beads prepared in Example 1 of the present invention under constant humidity flow conditions;

[0034] Fig.16 The figure is a graph showing the growth of ryegrass plants of Application Examples 1-3 and Comparative Examples 4-5 during drought stress treatment;

[0035] Fig.17 The graphs are the changes in soil water content and leaf water content of ryegrass plants of Application Examples 1-3 and Comparative Examples 4-5 during drought stress treatment;

[0036] Fig.18 The graphs are the changes of qN and Fv / Fm of ryegrass plants of Application Examples 1-3 and Comparative Examples 4-5 under drought stress;

[0037] Fig.19 The graphs of qP changes and ETR changes of ryegrass plants of Application Examples 1-3 and Comparative Examples 4-5 under drought stress;

[0038] Fig. 20 The enzyme activity diagram in the plant leaves of the ryegrass plants of Application Examples 1-3 and Comparative Examples 4-5;

[0039] Fig.21 The diagram of rhizosphere soil enzyme activity in the soil of Application Example 3 and Comparative Example 5;

[0040] Fig. 22This is a graph showing the water absorption performance of the SCLP gel beads prepared in Example 1 of the present invention at different humidity levels. DETAILED DESCRIPTION

[0041] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.

[0042] Example 1

[0043] A method for preparing a natural biomass water-retaining gel for collecting and retaining water in arid soil, characterized in that it comprises the following steps:

[0044] Step 1, dissolving 2 g of sodium alginate and 1 g of carboxymethyl cellulose in 100 g of deionized water, stirring and mixing, then adding 0.56 g of lithium chloride, and then, under stirring, continuing to add 10 g of N-isopropylacrylamide monomer (NIPAM) and 6 mg of N,N'-dimethylbisacrylamide to obtain a mixture;

[0045] Step 2: The mixture was bubbled with Ar gas for 60 min to remove residual oxygen, and then 12 uL of N,N,N',N'-tetramethylethylenediamine, 6 mg of polymerization accelerator MBA, and 20 mg of ammonium persulfate as an initiator were added in sequence, and the polymerization was completed in a beaker at room temperature for 24 h to obtain a mixed gel;

[0046] Step 3: Use microfluidics to drop the mixed gel into a 0.34 g / mL calcium chloride aqueous solution at 60°C and react for 12 hours to obtain hydrogel beads, then wash the hydrogel beads with deionized water, and finally vacuum freeze-dry at -60°C for 48 hours to obtain SCLP gel beads, i.e., natural biomass water-retaining gel.

[0047] Figure 1 Synthesis process of water-retaining gel from natural biomass. Figure 2 The scanning electron microscope images of SCLP gel beads at different magnifications show a loose, porous internal structure that is conducive to capturing more water molecules from the air later. Figure 3 It can be seen that C, N, O, and Cl are evenly distributed throughout the porous structure, confirming the uniform polymerization of various polymer monomers in the hydrogel beads; Figure 4 It can be seen that the FT-IR spectrum of SCLP gel beads has the peaks at 3340 and 2890 cm -1 There are absorption bands at 1640 and 1060 cm -1Several characteristic peaks were further observed at 2930 cm-1, corresponding to the CO stretching vibration of SA and CMC and the symmetric stretching vibration of the COC bond of the C carboxyl group. It is worth noting that the SCLP gel beads showed two new characteristic peaks, which were attributed to the CH stretching vibration (2930 cm-1). -1 ) and amide I (1640 cm -1 ), further confirming the successful modification of NIPAM on SCL hydrogel beads; Figure 5 It can be seen that the XRD pattern of the original SC exhibits a broad band at 23 due to its amorphous nature. The diffraction peak at 22 of the SCLP gel beads is broader than that of the original SC, indicating that the hydrophilic backbone (SA and CMC) has good miscibility with PNIPAM. After integrating lithium chloride into the SC+PNIPAM gel network, no diffraction peak of crystalline lithium chloride was detected due to the relatively low concentration of crystalline lithium chloride in the hydrophilic backbone; Figure 6-Figure 7 It can be seen that the main components on the surface of SCLP gel beads are O1s, N 1s, Ca 2p, C 1s and Cl2p, with binding energies of 532.08, 399.07, 347.38, 285.08 and 198.05 eV, respectively. The C1s XPS spectrum of SCLP gel beads can be consistent with the three components, namely CC at 248.80 eV, CN at 286.38 eV and NC=O at 287.78 eV ( Figure 7 Left), further confirming that PNIPAM was successfully grafted onto SC; the main characteristic peaks at 399.28 eV and 401.38 eV were found in the high-resolution N1s spectrum of SCLP gel beads, corresponding to -NC and NO ( Figure 7 In addition, the O1s spectrum of SCLP gel beads further confirmed that the hydrogel beads are rich in oxygen-containing functional groups ( Figure 7 right).

[0048] Example 2

[0049] The difference between this embodiment and embodiment 1 is that the added amount of NIPAM is 5 g, and the other contents are consistent with those of embodiment 1.

[0050] Example 3

[0051] The difference between this embodiment and embodiment 1 is that the added amount of NIPAM is 15 g, and the rest is consistent with embodiment 1.

[0052] Example 4

[0053] The difference between this embodiment and embodiment 1 is that the added amount of NIPAM is 20 g, and the rest is consistent with embodiment 1.

[0054] The swelling performance of the SCLP gel beads prepared in Examples 1-4 was tested at different temperatures. The results are as follows: Figure 8 As shown in the figure, the results show that when the NIPAM concentration is 10wt% (i.e., the addition amount is 10g) (corresponding to Example 1), the maximum swelling rate of SCLP gel beads at room temperature can reach 993%. When the temperature exceeds the lower critical solution temperature (LCST, 33°C), the SCLP gel beads can release more than 50% of the water captured from the air, and at 70°C, the SCLP gel beads can release more than 95% of the water. Fig. 9 It can be seen that when the temperature is 25°C, the SCLP gel beads have good hydrophilicity; when the temperature rises to 80°C, the SCLP hydrogel beads have obvious hydrophobicity, indicating that the introduction of PNIPAM can effectively achieve the hydrophilic-hydrophobic conversion of the gel beads by adjusting the temperature.

[0055] Example 5

[0056] A method for preparing a natural biomass water-retaining gel for collecting and retaining water in arid soil, characterized in that it comprises the following steps:

[0057] First, lithium chloride is modified by:

[0058] S1, dissolving 10g of lithium chloride in ethanol, heating and stirring until the lithium chloride is completely dissolved to prepare a lithium chloride solution with a concentration of 60wt%, then adding 3g of dopamine thereto, and keeping the reaction at 80°C for 8h to obtain a polydopamine-lithium chloride gel;

[0059] S2. The polydopamine-lithium chloride gel is carbonized at 600°C for 1 hour. After the carbonization is completed, it is argon plasma etched with an etching time of 120 seconds, a power of 100 W, and a pressure of 40 Pa to obtain modified lithium chloride.

[0060] Step 1, dissolving 2 g of sodium alginate and 1 g of carboxymethyl cellulose in 100 g of deionized water, stirring and mixing, then adding 0.56 g of modified lithium chloride, and then, under stirring, continuing to add 10 g of N-isopropylacrylamide monomer (NIPAM) and 6 mg of N,N'-dimethylbisacrylamide to obtain a mixture;

[0061] Step 2: The mixture was bubbled with Ar gas for 60 min to remove residual oxygen, and then 12 uL of N,N,N',N'-tetramethylethylenediamine, 6 mg of polymerization accelerator MBA, and 20 mg of ammonium persulfate as an initiator were added in sequence, and the polymerization was completed in a beaker at room temperature for 24 h to obtain a mixed gel;

[0062] Step 3: Use microfluidics to drop the mixed gel into a 0.34 g / mL calcium chloride aqueous solution at 60°C and react for 12 hours to obtain hydrogel beads, then wash the hydrogel beads with deionized water, and finally vacuum freeze-dry at -60°C for 48 hours to obtain SCLP gel beads, i.e., natural biomass water-retaining gel.

[0063] The water absorption performance of the SCLP gel beads prepared in this example at different humidity levels was tested. Fig. 22 As shown, it can be seen that in this embodiment, due to the addition of modified lithium chloride, the ability of the SCLP gel beads finally obtained to absorb water in the atmosphere at different humidity levels is improved, especially in a short time and at low humidity, the water absorption is greatly improved. This is because the polydopamine-lithium chloride gel formed by lithium chloride and dopamine is carbonized and treated with argon plasma to form a porous structure, and the specific surface area is greatly increased, which helps to increase the contact area between lithium chloride and water in the atmosphere, thereby improving its water absorption capacity.

[0064] Comparative Example 1:

[0065] The difference between this comparative example and Example 1 is that NIPAM is not added, and the other steps are consistent with Example 1, and finally the gel beads without PNIPAM, namely SCL, are obtained. The hygroscopic capacity of SCL is the same as that of the SCLP gel beads obtained in Example 1 of the present invention, but since NIPAM is not introduced, it is difficult to desorb the adsorbed water or the desorption is incomplete.

[0066] Comparative Example 2:

[0067] The difference between this comparative example and Example 1 is that lithium chloride (LiCl) is not introduced during the preparation process, and the other steps are consistent with Example 1. Finally, gel beads free of LiCl are obtained, and the adsorption capacity of the hydrogel without the introduction of LiCl is significantly reduced.

[0068] Comparative Example 3:

[0069] The difference between this comparative example and Example 1 is that lithium chloride (LiCl) and NIPAM are not introduced during the preparation process, and the other steps are consistent with Example 1. Finally, SC gel beads free of LiCl and NIPAM are obtained, which basically do not absorb water or have insignificant adsorption capacity.

[0070] Fig.10 TG curves of Example 1, Comparative Examples 1, 3 and PNIPAM. Fig.10It can be seen that for SC gel, the second weight loss stage occurs at 200-700 °C, which is due to the thermal decomposition of biomass materials. The second weight loss onset temperature of SCL is higher than that of SC, mainly due to the combination with hygroscopic salts. For PNIPAM, the second weight loss at 350-430 °C corresponds to the decomposition of PNIPAM polymer chains, while for SCLP gel beads, the second weight loss at 270-420 °C corresponds to the rapid decomposition of PNIPAM and the gradual decomposition of SCL. Fig.11 is the compressive stress-strain curve of Example 1 and Comparative Examples 1 and 3. Fig.11 It can be seen that SCLP gel beads have better mechanical properties than SC and SCL.

[0071] After the SCLP gel beads were prepared by the method of Example 1, the water absorption performance of the SCLP gel beads at different humidity levels was tested as follows:

[0072] Indoor measurements: Water vapor sorption of all samples was evaluated at room temperature (25°C) in a greenhouse with a controlled relative humidity RH of 30-90%; during the moisture sorption process, the hydrogels were weighed once every hour to record their mass changes.

[0073] Outdoor measurements: At night, SCLP gel beads were placed on a windowsill to collect water from the atmosphere; during the day, saturated SCLP beads were heated under a real sky for solar evaporation; a high-precision electronic balance was used to record the mass change of the SCLP beads in real time; a thermometer and hygrometer were used to automatically monitor temperature and relative humidity; and water absorption and release were calculated based on the mass change and initial weight.

[0074] The water absorption of the hydrogel is calculated as follows:

[0075] Water vapor adsorption = m i -m0 / m0*100%

[0076] Among them, m i is the weight of SCLP gel beads after moisture absorption at different times, and m0 is the original dry weight of SCLP gel beads.

[0077] The test results are as follows Fig.12 As shown, the results indicate that at 90% humidity, the saturated adsorption capacity is 990% within 600 min.

[0078] The water vapor adsorption-desorption cycle of SCLP gel beads was then tested to evaluate the performance stability of the material. Fig.13 As shown, the results indicate that the water absorption of SCLP gel beads did not decrease significantly after 10 adsorption-desorption cycles.

[0079] Since atmospheric water collection usually occurs outdoors, the moisture collection and release performance of SCLP gel beads under natural conditions was further tested. At night (when the air humidity is high), the pre-dried SCLP will absorb moisture from the atmosphere. The test results are shown in Figure 2. Fig.14 As shown, from Fig.14 It can be seen that the water absorption rate of SCLP gel beads reached saturation at around 9 am the next day, with a maximum water absorption rate of 700%. On sunny days, the relative humidity of the air gradually decreased from 71% at 7 o'clock to a minimum of 30% at 15 o'clock. At the same time, the outdoor temperature also increased from 15℃ at 7:00 to 30℃ at 15:00. At this stage, the pre-adsorbed saturated SCLP gel beads began to release water due to the increase in temperature and the decrease in humidity. The water content of SCLP gel beads gradually decreased from 596% (7:00) to 310% (15:00), indicating that SCLP gel beads have good water release ability in the presence of temperature-sensitive material-PNIPAM. When the sun sets and the relative humidity (RH) of the air increases again, the SCLP gel beads start a new round of collecting water from the atmosphere. During the 36h outdoor atmospheric water collection period, two water absorption processes and one water release process were recorded, showing the great potential of SCLP gel beads in atmospheric water collection in natural environments.

[0080] In addition, the water vapor adsorption performance of SCLP gel beads under constant humidity flow conditions was further tested using a dynamic suction system. The test results are shown in the figure below. Fig.15 As shown, from Fig.15 It can be seen that with the increase of humidity, the adsorption rate of SCLP gel beads with a porous network structure increased significantly, reaching 0.252 g / g at 90% RH.

[0081] Application Example 1

[0082] The SCLP gel beads prepared in Example 1 were added to the dry soil in an amount of 0.5 g / 5 g soil. The SCLP gel beads were applied to the topsoil, and then ryegrass seeds were planted in the soil. After germination, they were thoroughly watered once to ensure the survival of the seedlings. After the first thorough watering, the ryegrass seedlings were subjected to drought stress for 10 days, and the growth of the seedlings was observed.

[0083] Application Example 2

[0084] The SCLP gel beads prepared in Example 1 were added to the dry soil in an amount of 1 g / 5 g of soil. The SCLP gel beads were applied to the topsoil, and then ryegrass seeds were planted in the soil. After germination, they were thoroughly watered once to ensure the survival of the seedlings. After the first thorough watering, the ryegrass seedlings were subjected to drought stress for 10 days, and the growth of the seedlings was observed.

[0085] Application Example 3

[0086] The SCLP gel beads prepared in Example 1 were added to the dry soil in an amount of 2 g / 5 g soil. The SCLP gel beads were applied to the topsoil, and then ryegrass seeds were planted in the soil. After germination, they were thoroughly watered once to ensure the survival of the seedlings. After the first thorough watering, the ryegrass seedlings were subjected to drought stress for 10 days, and the growth of the seedlings was observed.

[0087] Comparative Example 4

[0088] The SC gel beads prepared in Comparative Example 3 were added to the dry soil in an amount of 2 g / 5 g of soil. The SCLP gel beads were applied to the topsoil, and then ryegrass seeds were planted in the soil. After germination, they were thoroughly watered once to ensure the survival of the seedlings. After the first thorough watering, the ryegrass seedlings were subjected to drought stress for 10 days, and the growth of the seedlings was observed.

[0089] Comparative Example 5

[0090] Ryegrass seeds were planted in normal soil. After germination, they were watered thoroughly once to ensure the survival of the seedlings. After the first thorough watering, the ryegrass seedlings were subjected to drought stress for 10 days to observe the growth of the seedlings (CK treatment).

[0091] During the drought stress treatment of Application Examples 1-3 and Comparative Examples 4-5, relevant parameters were measured every 2 days according to the following method, and the above parameters were measured 3 times for each group.

[0092] Determination of soil moisture content: Drying method test was used. About 5 grams of soil was taken for each treatment, placed in an aluminum box, dried in an oven at 105°C, cooled naturally to room temperature, and then weighed. The calculation formula is as follows:

[0093] Soil moisture content% = (m1-m2) / m2*100%

[0094] Among them, m1 represents the mass of wet soil, g; m2 represents the mass of dry soil, g.

[0095] Determination of leaf moisture content: The drying method was used for the test. Leaf samples were collected at 9 am on sunny days. At each sampling point, the fresh needles obtained were washed as much as possible and weighed in distilled water. After 24 hours of storage in the dark, the needles were removed, the water on the leaves was sucked out with filter paper, and then weighed with a saturated weight. The green matter was deoxidized at 105°C for 15 minutes and then dried in an explosion oven at 90°C for 8 hours. After cooling to room temperature, the dry matter was weighed and repeated 3 times. The calculation formula is as follows:

[0096] Leaf moisture content% = (W1-W0) / (W2-W0)*100%

[0097] Among them, W0 represents dry weight, g; W1 represents fresh weight, g; W2 represents saturated weight after absorption, g.

[0098] Determination of plant enzyme activity: Leaf samples (0.1 g) were placed in a precooled mortar and ground with 0.5 mL of precooled phosphate buffer to obtain a tissue homogenate. Then, the tissue homogenate was centrifuged at 10,000 rpm for 10 min at 4°C, and the supernatant was used to determine the antioxidant enzyme activity. The three antioxidant enzymes, superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT), were assayed using a kit (Solebol Biotechnology Co., Ltd., China).

[0099] Soil enzyme activity assay: Soil was air-dried before measuring enzyme activities. Catalase activity (S-CAT) was expressed as 0.1 mol / L potassium permanganate / (hg). Phosphatase activity (S-ACP) was determined by colorimetry, and soil urease (S-UE) was detected using a kit (SuBo Biotechnology Co., Ltd., China).

[0100] Determination of chlorophyll fluorescence parameters: The measurement was carried out at 8:30 am every two days, and each treatment was repeated 3 times. Before the measurement, the plants were placed in the dark for 1 hour, and the chlorophyll fluorescence parameters were measured using a dual-channel modulated chlorophyll fluorescence spectrometer DUAL-PAM-100 (Heinz Woltz, Germany). The non-photochemical quenching coefficient (qN), photochemical quenching coefficient (qP), PSII maximum photochemical efficiency (Fv / Fm) and electron transfer efficiency (ETR) were recorded in the system. All parameters were completed on the same day.

[0101] Determination of rhizosphere soil bacterial community structure: The collected rhizosphere soil was subjected to high-throughput sequencing analysis. 1 g of rhizosphere soil was collected from each treatment group and immediately frozen in liquid nitrogen for subsequent studies. Total genomic DNA was extracted using a DNA extraction kit according to the DNA extraction instructions. The concentration of DNA was verified using NanoDrop and agarose gel. PCR amplification was performed using genomic DNA as a template using barcoded primers and Tks Gflex DNA polymerase (Takara).

[0102] Fig.16 The growth of ryegrass plants of Application Examples 1-3 and Comparative Examples 4-5 during drought stress treatment is shown in FIG. Fig.16 It can be seen that after 10 days of drought stress, the ryegrass seedlings in the CK group showed signs of wilting and collapse. However, the ryegrass in the different SCLP gel bead treatment groups grew normally, among which the ryegrass in the SCLP gel bead treatment group (2g) grew the best.

[0103] Fig.17The graphs of soil water content and leaf water content changes of ryegrass plants of Application Examples 1-3 and Comparative Examples 4-5 during drought stress treatment are shown in FIG. Fig.17 It can be seen that the soil moisture content and leaf moisture content of the SCLP treatment group (2g) are the highest, which are 28% and 40% respectively. This also confirms that the addition of SCLP provides the necessary moisture for the growth of plants, which is beneficial to the normal development and growth of plants. Therefore, the ryegrass in the SCLP gel bead treatment group (2g) grows best.

[0104] Fig.18 is a graph showing changes in qN and Fv / Fm of ryegrass plants of Application Examples 1-3 and Comparative Examples 4-5 under drought stress, Fig.19 The graphs are the changes in qP and ETR of the ryegrass plants of Application Examples 1-3 and Comparative Examples 4-5 under drought stress. Figure 18-19 It can be seen that the values ​​of qP and ETR show a downward trend as the duration of drought stress increases, mainly due to the effect of water shortage on plant photosynthesis, reducing the participation of water molecules in light reactions, resulting in a decrease in qP and ETR values. As drought stress increases, qN and Fv / Fm values ​​show a trend of first increasing and then decreasing. The above phenomenon is due to the activation of the photoprotection mechanism by plants in the early stage of drought to increase qN and Fv / Fm in response to stress. Compared with the CK group, after adding 2g SCLP gel beads, the qP, qN, ETR and Fv / Fm values ​​did not decrease significantly, indicating that the introduction of SCLP gel beads can capture water from the atmosphere and alleviate the weakening of photosynthesis caused by drought.

[0105] Fig. 20 The enzyme activity diagram in the plant leaves of the ryegrass plants of Application Examples 1-3 and Comparative Examples 4-5 (SOD in the diagram is superoxide dismutase, POD is peroxidase, and CAT is catalase); Fig.21 Figure 3 is a diagram of rhizosphere soil enzyme activity in the soil of Application Example 3 and Comparative Example 5 (in the figure, S-UE is soil urease, S-NP is soil neutral phosphatase, and S-CAT is soil dehydrogenase). Figure 20-21 It can be seen that the activities of POD, SOD and CAT in the leaves and soil of plants treated with SCLP gel beads were higher than those in the control group, and the activity of the SCLP treatment group (2g) was the highest. Therefore, an appropriate amount of SCLP gel beads can regulate soil moisture, improve the growth environment of plants, thereby increasing the activity of defense enzymes and maintaining normal metabolism of plants.

[0106] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.

Claims

1. A method for preparing a natural biomass water-retaining gel for collecting and retaining water in arid soil, characterized in that: The following steps are involved: Step 1, dissolving sodium alginate and carboxymethyl cellulose in deionized water, stirring and mixing, then adding lithium chloride, and then continuing to add N-isopropylacrylamide monomer and N,N'-dimethylbisacrylamide under stirring to obtain a mixture; Step 2: bubbling the mixture with Ar gas, and then sequentially adding N,N,N',N'-tetramethylethylenediamine, a polymerization accelerator and ammonium peroxodisulfate as an initiator, completing polymerization at room temperature to obtain a mixed gel; Step 3: Drop the mixed gel into a calcium chloride aqueous solution at 60° C. by microfluidics and react for a period of time to obtain hydrogel beads, then wash the hydrogel beads with deionized water, and finally vacuum freeze-dry to obtain a natural biomass water-retaining gel.

2. The method for preparing the natural biomass water-retaining gel for collecting and retaining water in arid soil according to claim 1, characterized in that: In the step 1, the mass ratio of sodium alginate, carboxymethyl cellulose, deionized water, lithium chloride, N-isopropylacrylamide monomer, and N,N'-dimethylbisacrylamide is 2:1:100:0.56:5-20:0.

006.

3. The method for preparing the natural biomass water-retaining gel for collecting and retaining water in arid soil according to claim 1, characterized in that: In the step 2, the Ar gas bubbling time is 60 minutes, the addition amount of N,N,N',N'-tetramethylethylenediamine is 12 to 60 μL, the polymerization accelerator is N,N'-methylenebisacrylamide cross-linking agent, the addition amount is 6 to 24 mg, the addition amount of ammonium persulfate is 20 to 80 mg, and the polymerization time is 24 hours.

4. The method for preparing the natural biomass water-retaining gel for collecting and retaining water in arid soil according to claim 1, characterized in that: In the step 3, the concentration of the calcium chloride aqueous solution is 0.34 g / mL, the reaction is 12 hours, the vacuum freeze drying temperature is -60°C, and the freezing time is 48 hours.

5. The method for preparing the natural biomass water-retaining gel for collecting and retaining water in arid soil according to claim 1, characterized in that: First, lithium chloride is modified by: S1, dissolving lithium chloride in ethanol, heating and stirring until the lithium chloride is completely dissolved to prepare a lithium chloride solution, then adding dopamine thereto, keeping the temperature for a period of time to react, and obtaining a polydopamine-lithium chloride gel; S2. Carbonizing the polydopamine-lithium chloride gel at high temperature, and then performing argon plasma etching after the carbonization is completed to obtain modified lithium chloride.

6. The method for preparing the natural biomass water-retaining gel for collecting and retaining water in arid soil according to claim 5, characterized in that: In S1, the concentration of the prepared lithium chloride solution is 50-80wt%, the mass ratio of lithium chloride to dopamine is 1:0.2-0.5, the reaction temperature is 75-110°C, and the reaction is kept warm for 6-12h.

7. The method for preparing the natural biomass water-retaining gel for collecting and retaining water in arid soil according to claim 5, characterized in that: In S2, the high-temperature carbonization temperature is 500-800°C, the carbonization time is 0.5-2h, the argon plasma etching time is 5-500s, the power is 60-120W, and the pressure is 20-80Pa.

8. An application of the natural biomass water-retaining gel prepared by the preparation method according to any one of claims 1 to 7 in water collection and water retention in arid soil, characterized in that: The natural biomass water-retaining gel is used in arid soil to improve the water absorption and temperature sensitivity of the arid soil.

Citation Information

Patent Citations

  • Method for absorbing uranium with uranium template ion imprinted ploy(N-isopropyl acrylamide) / chitosan interpenetrating polymer network hydrogel

    CN104761747A

  • Temperature-sensitive NIPAM / SA hydrogel, preparation method thereof and essence and fragrance slow-release system

    CN117467079A

  • Hydrogel and uses thereof as a substrate for growing plants

    US20210040272A1

Cited By

  • Multi-index fusion leaf vegetable freshness grading method and spectrum detection model

    CN122193165A